Environmentally friendly usage of the soils and fertility losses cost estimation - Yevsieieva, M. V.; Vrublevska, B. M.; Handzii, N. V.; Hordiienko, O. A.; Zvuzdetska, N. S. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The results of the ecological-agrochemical analysis of main soils types of the agricultural enterprise of the Vinnitsa region are presented in the research. The cost estimation of the necessary fertility components is realized. The propositions aimed at soils ecological condition improvement are elaborated.